2017
DOI: 10.3758/s13421-017-0695-2
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory for low- and high-frequency-filtered emotional faces: Low spatial frequencies drive emotional memory enhancement, whereas high spatial frequencies drive the emotion-induced recognition bias

Abstract: This article deals with two well-documented phenomena regarding emotional stimuli: emotional memory enhancement-that is, better long-term memory for emotional than for neutral stimuli-and the emotion-induced recognition bias-that is, a more liberal response criterion for emotional than for neutral stimuli. Studies on visual emotion perception and attention suggest that emotion-related processes can be modulated by means of spatial-frequency filtering of the presented emotional stimuli. Specifically, low spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…In recognition tests, participants indicate whether a stimulus is presented for the first time ('new') or whether it has been presented before ('old'), and emotional stimuli are more likely to be correctly recognized as old (i.e., a hit). In several previous studies on recognition memory for fearful faces, old/new discrimination was better for fearful than positive/happy and/or neutral faces (Fischer et al, 2007;Righi et al, 2012;Rohr et al, 2017;Sergerie et al, 2006;Wang, 2013).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In recognition tests, participants indicate whether a stimulus is presented for the first time ('new') or whether it has been presented before ('old'), and emotional stimuli are more likely to be correctly recognized as old (i.e., a hit). In several previous studies on recognition memory for fearful faces, old/new discrimination was better for fearful than positive/happy and/or neutral faces (Fischer et al, 2007;Righi et al, 2012;Rohr et al, 2017;Sergerie et al, 2006;Wang, 2013).…”
Section: Introductionmentioning
confidence: 72%
“…In line with previous findings (Righi et al, 2012) and with the liberal response bias for fearful faces, participants in both studies were also quicker to correctly decide that fearful compared to neutral faces were old, but slower to correctly decide that fearful compared to neutral faces were new (significant in Study 1). Although previous studies have observed enhanced recognition memory for fearful faces (Fischer et al, 2007;Righi et al, 2012;Rohr et al, 2017;Sergerie et al, 2006;Wang, 2013), a liberal response for fearful faces has been observed instead in prior research as well (Rohr et al, 2017). Interestingly, the latter study examined the role of spatial frequencies in recognition memory for emotional faces and found that low spatial frequencies drive the enhanced recognition memory for fearful faces, whereas high spatial frequencies drive the liberal response bias for fearful faces.…”
Section: Tablementioning
confidence: 77%
“…Johansson et al (2004) failed to observe an effect of emotion on discrimination or bias with know responses. In a recent investigation, Rohr et al (2017) observed EEM effects across direct and indirect encoding tasks for both recollection and familiarity on indices of discrimination and response bias, as well as across negative (fear) and positive (happy) facial stimuli.…”
mentioning
confidence: 96%